Development of a mapping approach encompassing most fluvial processes: Lessons learned from the freedom space for rivers concept in Quebec (Canada) - Massé, Simon; Demers, Sylvio; Besnard, Clément; Buffin‐Bélanger, Thomas; Biron, Pascale M.; Choné, Guénolé; Massey, William (River Research and Applications, 2020)
Abstract The consensus around the need for a shift in river management approaches to include more natural processes is steadily growing amongst scientists, practitioners, and governmental agencies. The freedom space for rivers concept promotes the delineation of a single space that integrates multiple fluvial dynamics such as floods, lateral migration, channel avulsions, and riparian wetlands connectivity. The objective of this research is to assess the validity of the hydrogeomorphological approach to delineate the freedom space for an extensive sampling of river reaches, covering 167 km, in contrasting watersheds in Quebec (Canada). Comparative analysis was conducted on the relative importance of erosion and flood processes on the freedom space delineation for various fluvial types. Semiautomated tools based on light detection and ranging (LiDAR) digital elevation models were also tested on an additional 274 km of watercourses to facilitate freedom space mapping over extensive zones and for highly dynamics environments such as alluvial fans. In the studied reaches, flood and erosion processes occur respectively, on average, in a space equivalent to 2.6 and 20.6 channel widths. In unconfined landscapes, flood processes represent an area up to almost four times the area of erosion processes expected in a 50‐year period. In partly confined and confined environments, erosion processes are more likely to exceed flooding zone, and therefore need to be integrated in the mapping. This study helps better determine the conditions for which the full methodology of freedom space mapping is required or where semiautomated methods can be used. It provides useful guidelines for the implementation of the freedom space approach.
Keywords: Ouvrage_Collectif_Numéro1

Pandémie et inondations ne font pas bon ménage : comment relever ce double défi - Gousse-Lessard, Anne-Sophie; Souza, Danielle Maia de; Maltais, Danielle; Généreux, Mélissa; Gachon, Philippe; King, Suzanne; Buffin-Bélanger, Thomas (The Conversation, 2020)
La pandémie transforme la manière avec laquelle la sécurité civile a l’habitude de procéder devant les aléas. Nos réseaux de soutien communautaire seront mis à rude épreuve s’il y a des inondations.
Keywords: Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Site_internet_RIISQ